Production of N, P, and K humates from palm oil mill effluent sludge and their effects on corn growth - Shamsuddin, Rosliza (2011)
Substantial loss through ammonia volatilization from surface-applied urea reduces urea-N use efficiency in plant production, pollutes environment and burdens economy. This problem could be minimized through the use of agricultural wastes such as palm oil mill effluent (POME) sludge. POME sludge could reduce this volatilization in view of its acidic nature and high cation exchange capacity (CEC) present in it the form of humic acids (HA) and fulvic acids (FA). The objectives of this study were to: (I) Evaluate if N, P and K humates produced from POME sludge could minimize ammonia volatilization from urea as well as improving retention of soil exchangeable ammonium and nitrates in laboratory condition and (ii) Evaluate the effect of N, P, and K humates on soil pH, exchangeable ammonium, available nitrate; N, P, and K concentrations, their uptake and use efficiency in corn (Zea mays) cultivation under greenhouse condition. HA and FA were isolated from air-dried POME sludge using 0.5 M KOH and 6 N H2SO4. Daily ammonia loss was measured for 15 days using a closed-dynamic air flow system. Ammonia released was estimated using boric acid indicator traps which were replaced every 24 h and titrated with 0.01 N HCl. Soil samples were evaluated for pH, exchangeable ammonium and available nitrate. Under greenhouse condition, formulated fertilizers were applied 10 days after planting (DAP) in each pot containing 10 kg of soil. Soil and plant samples (stems, leaves and roots) were sampled at 31 DAP. Soil samples were analyzed for pH, ammonium and nitrate content. Plant samples were analyzed for dry matter production, N, P, and K concentrations, N, P, and K uptake, and their use efficiency. From the laboratory study, Urea-TSP-MOP-HA, Urea-TSP-MOP, urea-FA, Urea-TSP-MOP-FA, Ureaacidified (HA+FA) and Urea-TSP-MOP-acidified (HA+FA) mixtures significantly reduced ammonia by 13, 20, 23, 30%, and 100% (of the N added as urea), respectively. These treatments also caused significant retention of soil exchangeable ammonium. When the treatments were further tested in a greenhouse, Urea-TSPMOP, urea-FA, Urea-TSP-MOP-Humin, Urea-TSP-MOP-acidified(HA+FA), Urea- TSP-MOP-FA and Urea-TSP-MOP-HA mixtures had significant effect on dry matter production, N, P, and K uptake and use efficiency of the test crop (Zea mays) compared to urea alone. Urea amended with HA, FA, TSP and MOP minimized ammonia volatilization, as well as improving soil exchangeable ammonium, and urea-N use efficiency. It must be stressed that results obtained in the laboratory and greenhouse experiments may only be applicable to similar acid soils.